TURMERIC EXTRACT AND SALT FOR WOUND HEALING PROCESS - amrullah, Syahid; Pratama, Kharisma; Kurniawan, Rahmad; Hartono, Hartono; Pradika, Jaka; Saputra, Ari (Jurnal Keperawatan dan Kesehatan, 2023)
Turmeric is an herbal plant that is believed to accelerate the wound healing process. Scientifically, turmeric has been proven to have anti-inflammatory and antibacterial effects. This study aimed to determine the effectiveness of turmeric extract and salt on wound healing. This was experimental study. Experimental animals were divided into two groups, each group consisted of five white rats, each group was given treatment using (turmeric extract with salt and Normal Saline solution). The data were analyzed by using the Statistical Product and Service Solution Program (analysis of variance, Wilcoxon). This study showed that there were significant differences in the intervention group and the control group (P<0.05). However, The Mann withney test showed that there are the same results between the treatment group by Turmeric and Salt Extract (TSE) with the control group by Normal Saline Solution (NSS) and also showed that both treatments has the same function in accelerating wound healing process. There is a strong effect of using TSE treatment in wound care for wound healing process on white rats.